Prevalence and prognostic impact of cachexia among older patients with cancer: a nationwide cross‐sectional survey (NutriAgeCancer). Issue 6 (14th September 2021) - Poisson, Johanne; Martinez‐Tapia, Claudia; Heitz, Damien; Geiss, Romain; Albrand, Gilles; Falandry, Claire; Gisselbrecht, Mathilde; Couderc, Anne‐Laure; Boulahssass, Rabia; Liuu, Evelyne; Boudou‐Rouquette, Pascaline; Chah Wakilian, Anne; et al.
Abstract: Background: Nutritional impairment is common in cancer patients and is associated with poor outcomes. Only few studies focused on cachexia. We assessed the prevalence of cachexia in older cancer patients, identified associated risk factors, and evaluated its impact on 6 month overall mortality. Methods: A French nationwide cross‐sectional survey (performed in 55 geriatric oncology clinics) of older cancer patients aged ≥70 referred for geriatric assessment prior to treatment choice and initiation. Demographic, clinical, and nutritional data were collected. The first outcome was cachexia, defined as loss of more than 5% of bodyweight over the previous 6 months, or a body mass index below 20 kg/m 2 with weight loss of more than 2%, or sarcopenia (an impaired Strength, Assistance with walking, Rise from chair, Climb stairs and Falls score) with weight loss of more than 2%. The second outcome was 6 month overall mortality. Results: Of the 1030 patients included in the analysis [median age (interquartile range): 83 (79–87); males: 48%; metastatic cancer: 42%; main cancer sites: digestive tract (29%) and breast (16%)], 534 [52% (95% confidence interval: 49–55%)] had cachexia. In the multivariate analysis, patients with breast ( P < 0.001), gynaecologic ( P < 0.001), urinary ( P < 0.001), skin ( P < 0.001), and haematological cancers ( P = 0.006) were less likely to have cachexia than patients with colorectal cancer. Patients with upper gastrointestinal tract cancers (including liver and pancreatic cancers; P = 0.052), with previous surgery for cancer ( P = 0.001), with metastases ( P = 0.047), poor performance status (≥2; P < 0.001), low food intake ( P < 0.001), unfeasible timed up‐and‐go test ( P = 0.002), cognitive disorders ( P = 0.03) or risk of depression ( P = 0.005), were more likely to have cachexia. At 6 months, 194 (20.5%) deaths were observed. Cachexia was associated with 6 month mortality risk (adjusted hazard ratio = 1.49; 95% confidence interval: 1.05–2.11) independently of age, in/outpatient status, cancer site, metastatic status, cancer treatment, dependency, cognition, and number of daily medications. Conclusions: More than half of older patients with cancer managed in geriatric oncology clinics had cachexia. The factors associated with cachexia were upper gastrointestinal tract cancer, metastases, poor performance status, poor mobility, previous surgery for cancer, cognitive disorders, a risk of depression, and low food intake. Cachexia was independently associated with 6 month mortality.